The Perspective of the PMII Women's Corps (KOPRI) at UBJ on Women Smoking in the Series Gadis Kretek - Nabilah Mumtaz; Syahrul Hidayanto (CV. Era Digital Nusantara, 2026)
This study aims to examine the perspective of an external Islamic student organization, KOPRI PMII UBJ, on women smoking in the series Gadis Kretek. The study employs a qualitative approach with a descriptive method, and data were collected through observation, interviews, and documentation. The findings indicate that KOPRI PMII UBJ views women smoking in Gadis Kretek as no longer a taboo, but increasingly normalized due to cultural shifts and changes in societal mindsets, although some older generations still hold negative stigmas. KOPRI believes that women and men have equal rights to express themselves, including in the choice to smoke, and therefore gender-based discrimination is unjustified. They emphasize the importance of respecting individual decisions as long as they do not disturb others, and argue that women who smoke should not be automatically associated with negative character. Through the character Dasiyah in Gadis Kretek, the series portrays women as strong, independent, responsible, and empowered, offering a new perspective that challenges existing stigmas and suggests that negative views toward women smoking are not always relevant in contemporary society.